DEVELOPMENT OF A COLLECTION OF WOMEN'S LIGHT DRESSES TAKING INTO ACCOUNT THE CHARACTERISTICS OF THE CUSTOMER'S FIGURE - BABYCH, ANTONINA; TELUSHKA, SVITLANA; BITSENEVA, TETYANA (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The use of classic color and design solutions in the development of modern models of women's clothing in the "retro" style attracts the attention of fashion industry specialists, since fashion occasionally returns to our society due to the creation of stylized models of products with a reference to the past times of the 1920–1970. is traced by a chain of specific actions from the "birth" of an idea and the creation of a creative source to the execution of a sketch project with the selection of materials and accessories and the detailed development of the design of the products of the collection. The article researched and analyzed the issue of creating an assortment of modern dresses from different materials, taking into account the features of the customer's figure and consumer preferences. The types of female body shapes were analyzed. The article researched and analyzed the issue of creating an assortment of modern clothes for women of various purposes, designs and materials. The issue of constructivism in clothing design was investigated and analyzed. An analysis of Ukrainian brands of clothing manufacturers was carried out with the help of Google surveys of consumers of different age groups. The expediency of this development has been theoretically proven.The results of marketing research on the possibility of using bold constructive ideas and color solutions in women's clothing in the "retro" style are given. A sketch project, 3D models of the range of the clothing collection of the women's range group have been developed. Design and technological documentation for products has been developed. An industrial sample of a light dress of the women's range of the developed collection was produced. The development was introduced into production at the FOP "A-style", Berdychiv. The expediency of this development has been proven theoretically and experimentally.
Keywords: assortment; figure type; design; manufacturability of the model; research; demand; product